Pengaruh Celebrity Endorser terhadap Prurcahe Intention melalui Brand Image sebagai Variabel Intervening pada pengguna kosmetik Wardah di Toko Kurnia probolinggo - Indah Faizah; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this research is to recognize the direct influence of the variable Celebrity Endorser on Purchase Intention, there is a direct influence of Celebrity Endorser on Purchase Intention, there is a direct influence on Brand Image on the Purchase intention, and there is an indirect influence of Celebrity Endorser against Purchase intention through the Brand Image as the intervening variables on Cosmetic Products. This study used a qualitative approach. The population and sample used in this study were Wardah cosmetics users at the Kurnia Probolinggo shop. The sampling technique uses accidental sampling technique. Meanwhile, the analytical method used in this study is path analysis.                           The results of this study provide empirical evidence that there is a direct influence of Celebrity Endorser on Purchase Intention, there is a direct influence of Celebrity Endorser on Purchase Intention, there is a direct influence of Brand Image on Purchase intention, and there are indirect effects of Celebrity Endorser on Purchase intention through Brand Image as a variable intervening. Kata Kunci : Celebrity Endorser, Purchase intention, Brand Image